Nurses' perception of the nursing process and its relationship with leadership - Karen Ariane Bär; Bianca dos Santos Lima; Gicelle Morais Martelle; Silvana Cruz da Silva; Margarida Reis dos Santos; Regina Gema Santini Costenaro (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to describe Nurses' perception of the Nursing Process and its relationship with leadership. Methods: action research conducted between September/2021 and April/2022 with nurses from a medium-sized hospital in southern Brazil. The data investigated, one of the stages of the method, was collected using the Focus Group technique and submitted to Strategic Focus Analysis. Results: three categories emerged from the organized and analyzed data, namely: Nursing Process: a tool that qualifies nursing care; Conditions that weaken the Nursing Process; and Strategies that enhance the Systematization of Nursing Care. Final Considerations: the perception of the Nursing Process and its relationship with leadership are not always understood as complementary themes. Although they recognize that the Nursing Process is sometimes imposed as normative, nurses do not perceive the importance of the role of the leader, who is considered a key player in conducting and boosting the Systematization of Nursing Care.